Impact of deglacial and Holocene AMOC changes on the mixed layer and deepwater hydrography of the subtropical North Atlantic - Repschlaeger, Janne (2013)
The Atlantic meridional overturning circulation (AMOC) transports warm saline water from low to high northern latitudes where it cools, sinks down and returns southward as deepwater flow. By the heat transfer from low to high latitudes, AMOC contributes in balancing the global energy budget and thus is an important part of global climate system. Within this study the impact of AMOC changes on surface and deepwater hydrography of the subtropical North Atlantic is investigated by the use of high-resolution sediment cores from a coring site located south of the Azores at the eastern flank of the Mid Atlantic Ridge. The Azores coring site is situated in the subtropical eastern North Atlantic (NA) at the boundary between warm Subtropical Gyre Water (STG) and temperate East North Atlantic Water (ENAW) at the surface. At depth the site is located at the interface between southern sourced Lower Deep Water (LDW) and North East Atlantic Deep Water (NEADW) that consists of a mixture of northern sourced Iceland-Scotland Overflow Water (ISOW) and Labrador Sea Water (LSW). Due to its location at water mass boundaries the coring position is ideal to reconstruct coupled surface and deepwater changes. Deglacial records in centennial to decadal resolution of changes in the mixed layer and the deepwater are established. Multiproxy sea surface temperature (SST) reconstructions using Mg/Ca surface of planktonic surface and subsurface dwelling foraminifera, the alkenone undersaturation index UK´37 and foraminifera transfer function (SIMMAX) are used to gain a reliable deglacial SST records from the subtropcial NA and to decipher environmental imprints other than temperature on SST reconstructions. The combination of these SST records with stable oxygen isotope records (δ18O) from planktonic surface and subsurface dwelling foraminifera are used to derive changes in the mixed layer salinity (18Ow-ice). Additionally, variations in the STG position are reconstructed by the use of foraminifera abundance data. Deglacial changes in ...